Next-Generation Sequencing in Newborn Screening: A Review of Current State - Remec, Ziga I.; Trebusak Podkrajsek, Katarina; Repic Lampret, Barbka; Kovac, Jernej; Groselj, Urh; Tesovnik, Tine; Battelino, Tadej; Debeljak, Marusa (Frontiers in Genetics, 2021)
Newborn screening was first introduced at the beginning of the 1960s with the successful implementation of the first phenylketonuria screening programs. Early expansion of the included disorders was slow because each additional disorder screened required a separate test. Subsequently, the technological advancements of biochemical methodology enabled the scaling-up of newborn screening, most notably with the implementation of tandem mass spectrometry. In recent years we have witnessed a remarkable progression of high-throughput sequencing technologies, which has resulted in a continuous decrease of both cost and time required for genetic analysis. This has enabled more widespread use of the massive multi-parallel sequencing. Genomic sequencing is now frequently used in clinical applications, and its implementation in newborn screening has been intensively advocated. Expansion of newborn screening has raised many clinical, ethical, legal, psychological, sociological, and technological concerns over the time. This review provides an overview of the current state of next-generation sequencing regarding newborn screening including current recommendations and potential challenges for the use of such technologies in newborn screening.